The Role of Non-Coding RNAs in Breast Cancer Drug Resistance - Tian, Jin-hai; Liu, Shi-hai; Yu, Chuan-yang; Wu, Li-gang; Wang, Li-bin (Frontiers in Oncology, 2021)
Breast cancer (BC) is one of the commonly occurring malignancies in females worldwide. Despite significant advances in the therapeutic, the mortality and morbidity still leads to low survival and poor prognosis due to the chemoresistance of BC. There are certain chemotherapeutics medicine often used for BC patients,including Anthracyclines, Taxanes, Docetaxel, Cisplatin, and Fluorouracil,et al. The chemoresistance mechanisms of these medicine are complicated and not been fully elucidated. It was reported that noncoding RNAs (ncRNAs), such as micro RNAs (miRNA), Long-chain noncoding RNAs (lncRNAs), and circular RNAs (circRNAs) performed key roles in regulating tumor development and mediating therapy resistance. But the mechanism of these ncRNAs in BC chemoresistance was different. This review aims to reveal the mechanism and potential function of ncRNAs in the chemoresistance of BC.